2016
DOI: 10.1016/j.learninstruc.2016.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Relations between the worked example and generation effects on immediate and delayed tests

Abstract: The contradiction between the worked example effect that occurs when learners presented with more instructional guidance learn more than learners presented with less guidance and the generation effect that occurs when the reverse result is obtained can be resolved by the suggestion that the worked example effect is obtained using materials high in element interactivity, whereas simpler, low element interactivity materials result in the generation effect. A 2 (guidance: low vs. high) x 2 (element interactivity:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
66
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 73 publications
8
66
2
Order By: Relevance
“…To date, most of the studies supporting the generation effect considered simple learning contents, that is simple facts or procedures. Chen et al (2015Chen et al ( , 2016 compared learning by generation with learning by worked examples varying simple and complex contents. Their studies showed that for complex contents learning by worked examples (i.e., by demonstration) is more effective than learning by generation whereas for simple contents the reverse holds.…”
Section: Theoretical Perspectives On the Teaching And Learning Of Adamentioning
confidence: 99%
See 1 more Smart Citation
“…To date, most of the studies supporting the generation effect considered simple learning contents, that is simple facts or procedures. Chen et al (2015Chen et al ( , 2016 compared learning by generation with learning by worked examples varying simple and complex contents. Their studies showed that for complex contents learning by worked examples (i.e., by demonstration) is more effective than learning by generation whereas for simple contents the reverse holds.…”
Section: Theoretical Perspectives On the Teaching And Learning Of Adamentioning
confidence: 99%
“…As previously described in the model of Siegler and colleagues, the students have to learn a combination of different aspects like different strategies, their accurate and fluent use, their flexible use as well as criteria for which tasks a strategy is efficient. The findings of Rittle-Johnson and Kmicikewycz (2008) suggest a generation effect for the acquisition of strategies and their accurate and fluent use, whereas the findings of Chen et al (2015Chen et al ( , 2016 indicate that a teacher demonstration might be more effective in the complex case of the adaptive use of strategies. Hence, it is an open question whether instruction is more effective when students invent strategies and learn the adaptive use of strategies (as suggested) than a demonstration through explicit teaching.…”
Section: Theoretical Perspectives On the Teaching And Learning Of Adamentioning
confidence: 99%
“…PST 6 rejected what he/she described as "traditional didactic manner". In this regard PST 6 manifests the view that principles of learning, potentially emphasising facilitation and co-construction (alignment with "teaching pedagogy evidence"), are preferable to a more didactic approach favoured by the author and East Asian educators (e.g., Huang & Leung, 2004;Lai & Murray, 2012;Leung et al, 2015;Li, 2004), meta-data analysts (e.g., Hattie, 2009;Hattie & Donoghue, 2016), and cognitive load theorists (e.g., Chen et al, 2016;Kirschner, Sweller, & Clark, 2006;Sweller, 2016;Tricot & Sweller, 2014). It needs to be noted, however, that while the views of PST 6 provide a reasonably coherent justification for existing generic mathematics teacher education programs and curriculum courses/subjects, they are counter to those expressed by the majority of the pre-service teachers enrolled in the mathematics course informing this study.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, not only can an effect disappear using low element interactivity material but it can also reverse. Chen, Kalyuga, and Sweller (, ) obtained a conventional worked example effect using high element interactivity information but a reverse effect for low element interactivity information, providing a strong example of the element interactivity effect. This reverse of the worked example effect is called the generation effect and has been known for longer than the worked example effect.…”
Section: Cognitive Load Theorymentioning
confidence: 99%